IPad Audiometry in Canada's North: A Portable and Cost‐Effective Method for Hearing Screening. (2nd September 2014) - Rourke, Ryan; Bromwich, Matthew; Chan, David
Abstract : Objectives: Access to hearing health care is limited in many parts of the world. Specifically, many risk factors for hearing loss are present in the First Nations people of Canada's North. No research has been done to assess this populations hearing in over 3 decades. The aims of the study were: (1) Determine the prevalence of hearing loss in children in Baffin Island. (2) Demonstrate the use of asynchronous tele‐audiometry. (3) Conduct a cost‐benefit analysis of iPad audiometry in the Canadian Arctic. Methods: iPad audiometers were used to test hearing in 220 children ages 5‐11 years in Iqaluit, Nunavut, during 1 week in January 2014. Air conduction pure tones were obtained from each ear at frequencies of 500, 1000, 2000, and 4000 Hz. Children with hearing loss greater than 25 dB in at least 1 frequency were considered to have failed the hearing test and will be further tested with standard sound booth audiometry. Results: Preliminary analysis reveals a hearing loss prevalence of 15.5%. These children then received standard testing by an audiologist using standard sound booth audiometry and the results analyzed. A cost‐benefit analysis assessed the use of iPad audiometry in this remote location. Conclusions: This is the first study in over 30 years assessing the hearing of children in this region, and the first telemedicine audiometry in Canada using iPads. This type of testing is valuable for providing hearing health care for high risk populations in rural and remote areas at an affordable cost.